De hoofdvleugel van de kasteelruïne Valkenburg aan de Geul (Bulletin KNOB, 2010)
The ruin of Valkenburg castle (province of Limburg) is situated on a hill in the southernmost part of the Netherlands. Although various consolidations and archaeological activities took place in the past one and a half centuries, relatively little attention was paid to the building history of the main wing. At present this has been measured once again, whereby colours were attributed to the various building phases.The oldest phase (brown) dates back to the 13th century, but the main wing as such was built in the second quarter of the 14th century (coloured yellow). On one side a chapel with chevet is now visible, but previously this was a storage room, probably with a kitchen above it and above that a living space.With the arrival of the chapel the three original floors were converted into two floors. At the time of the Eighty Years’ War (1568-1648) the ground floor was divided by means of crosswalls (green), just as the floor above it. During this renovation the wall thickness was reduced on the level of the floor.The building history of the wing proves to be more complicated than was assumed so far. The ruin leaves many questions unanswered; various solutions continue to be possible.